Impact of Thyroid Dysfunction on Serum Cystatin C, Serum Creatinine and Glomerular Filtration Rate - Sinisa Stojanoski; Daniela Pop Gjorceva; Todor Gruev; Svetlana Ristevska-Miceva; Nevena Ristevska (Scientific Foundation Spiroski, 2011)
Aim. The aim of this cross-sectional, prospective, randomized, longitudinal study was to asses serum cystatin C (Cys C) and creatinine concentrations and glomerular filtration rate (GFR) in thyroid dysfunction. Material and Methods. We have measured Cys C, creatinine and GFR using the 99mTc-DTPA technique in 35 patients (26 females and 9 males; 43 ± 11 years), 15 with newly diagnosed hyperthyroidism (TSH < 0.07 mIU/L, fT4 > 24 pmol/L) and 20 with newly diagnosed hypothyroidism (TSH > 4.5 mIU/L, fT4 < 9 pmol/L), at baseline and when they became euthyroid (TSH 0.4-4.5 mIU/L, fT4 9–24 pmol/L). The patients had no history of kidney disease and were subdivided into 2 groups: age (>50 and <50 years) and fT4 (40-100 pmol/L; >100 pmol/L) – hyperthyroid and TSH (4.5 - 48 mIU/L; > 48 mIU/L) – hypothyroid group. Thirty five age- and sex-matched normal subjects served as controls. Results. Increased creatinine levels in hypothyroid patients 115 ± 12 μmol/L decreased after treatment to 95 ± 14 μmol/L and reduced values in hyperthyroid patients 53.6 ± 12 μmol/L increased after treatement to 75.2 ± 14 μmol/L (p<0.05). Cys C ranged from 0.88 ± 0.7 mg/L before to 1.24 ± 0.5 mg/ L after treatment in hypothyroid and 1.65 ± 0.5 mg/L before to 0.96 ± 0.5 mg/L after treatment in hyperthyroid patients (p<0.01). Hyperthyroid subjects exhibited significant increase in GFR ranging from 144.1 ± 18 mL/min before to 123.7 ± 24 mL/min after treatment. Hypothyroid group exhibited significant decrease in GFR ranging from 81.1 ± 28 mL/min before to 103.7 ± 24 mL/min after treatment (p<0.01). The significant difference between GFR values assessed by the isotope technique and values assessed by the serum markers indicates that further work needs to be performed to confirm which method is giving the true reflection of GFR in thyroid dysfunction.